LAYANAN KEGAWATDARURATAN U-GARUDA 112 SEBAGAI INOVASI PELAYANAN PUBLIK DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN KUDUS TAHUN 2019 - Fernandya Khoirina Muryatami; Dewi Erowati (Journal of Politic and Government Studies, 2020)
Kudus Regency has a public service effort that continues to be developed to provideeasy access for the community. One of the concepts of government management relating topolicy and development and followed by rapid technological development is theimplementation of services in the field of emergencies, namely the Emergency SingleNumber Service 112. This service is an integration between the central government throughthe Ministry of Communication and Information and the regencies / cities in Indonesia.Kudus Regency built this service under the name Garuda Unit 112. The task of this serviceis to receive telephone calls from the public regarding 24-hour emergency reports, so theresearch conducted by researchers was related to the implementation of realizing Garuda112 Service Unit innovations The method used was descriptive qualitative research methods, with data collection techniques through observation, interviews, and documentation studies. The subjects in this study were Kudus Regency Communication and Information Office, Regional Disaster Management Agency, Garuda Unit 112 Officers and the community. The focus in thisstudy was according to the theory of De Vreye: 1) Self Esteem, 2) Exceed expectation, 3)Recovery, 4) Vision, 5) Improve, 6) Care, 7) Empower.The research results obtained were: socialization is still minimal so that there arestill forms of complaints and many trial and error calls made by the community, thenetwork / application is often unstable,the characteristics or character possessed byoperators and Garuda Unit 112 officers are already good in serving the community butincoming reports are not all emergency reports.Keywords: Quality Dimensions of Emergency Service, Garuda Unit 112